The need for home-based geriatric care and physical, mental, and social functioning of seniors of over 65 years of age - Dziechciaż, Małgorzata; Wróblewska, Izabela M.; Talarska, Dorota; Chmielewski, Jarosław; Filip, Rafał; Szpringer, Monika (Medical Studies/Studia Medyczne, 2017)
Introduction: The increased percentage of seniors observed within society establishes new challenges for healthcare systems. Aim of the research : To estimate the need for geriatric, home-based care for people over 65 years of age living in rural areas, in the context of physical, mental, and social functioning. Material and methods: The research methods included the diagnostic poll method and direct observation. The following research tools were used: Barthel Index, Lawton Index, Abbreviated Mental Test Score by Hodkinson, Geriatric Depression Scale Short Form, and an authorial interview questionnaire. The criterion for home-based geriatric care was to be declared as a geriatric patient. The research was carried out among 504 people in the ages of 66 to 94 years (average: 77.41 years). Results: For home-based geriatric care, significantly more women than men were qualified (p < 0.01). The average age of respondents qualified for home-based geriatric care was higher than the age of other test subjects (p < 0.001). Subjects qualified for home-based geriatric care were more often widowed (p < 0.001) with incomplete primary education (p < 0.001) and substantially were living alone (p < 0.05). Among the people qualified for home-based geriatric care there were more multi-diseases, worsened agility to perform basic and complex daily life activities, and worsened cognitive and emotional performance (p < 0.001) than with other test subjects. Conclusions : For home-based geriatric care, a third of seniors living in rural areas were qualified. The need for home-based geriatric care was determined by suffering from multi-diseases, having functional, emotional, and cognitive disorders, progressing age, being female, having low education, and being widowed.